Inputs of disinfection by-products to the marine environment from various industrial activities: Comparison to natural production. (15th June 2022) - Grote, Matthias; Boudenne, Jean-Luc; Croué, Jean-Philippe; Escher, Beate I.; von Gunten, Urs; Hahn, Josefine; Höfer, Thomas; Jenner, Henk; Jiang, Jingyi; Karanfil, Tanju; Khalanski, Michel; Kim, Daekyun; et al.
Highlights: Overview on oxidative treatment processes for different industrial applications. Compilation of disinfection by-product types/concentrations in marine water uses. Estimation of global DBP inputs into marine water from different industries. Comparison of anthropogenic bromoform production to emissions from natural sources. Abstract: Oxidative treatment of seawater in coastal and shipboard installations is applied to control biofouling and/or minimize the input of noxious or invasive species into the marine environment. This treatment allows a safe and efficient operation of industrial installations and helps to protect human health from infectious diseases and to maintain the biodiversity in the marine environment. On the downside, the application of chemical oxidants generates undesired organic compounds, so-called disinfection by-products (DBPs), which are discharged into the marine environment. This article provides an overview on sources and quantities of DBP inputs, which could serve as basis for hazard analysis for the marine environment, human health and the atmosphere. During oxidation of marine water, mainly brominated DBPs are generated with bromoform (CHBr3 ) being the major DBP. CHBr3 has been used as an indicator to compare inputs from different sources. Total global annual volumes of treated seawater inputs resulting from cooling processes of coastal power stations, from desalination plants and from ballast water treatment in ships are estimated to be 470–800 × 10 9  m 3, 46 × 10 9  m 3 and 3.5 × 10 9  m 3, respectively. Overall, the total estimated anthropogenic bromoform production and discharge adds up to 13.5–21.8 × 10 6  kg/a (kg per year) with contributions of 11.8–20.1 × 10 6  kg/a from cooling water treatment, 0.89 × 10 6  kg/a from desalination and 0.86 × 10 6  kg/a from ballast water treatment. This equals approximately 2–6% of the natural bromoform emissions from marine water, which is estimated to be 385–870 × 10 6  kg/a. Graphical abstract: Image, graphical abstract